Study of fungal rhinosinusitis among Covid patients at a tertiary care hospital - Ashitha P; Chaya A K; A. Sangale; S. Chamalwad; R. Ingle; Baveja S (Elsevier, 2024)
Introduction: Fungal rhinosinusitis (FRS) is being reported with increasing frequency from around the world and has become an important concern in India following the Covid-19 pandemic (Saha et al., 2016). The objectives of the study were to study the clinical and radiological characteristics of fungal rhinosinusitis, and to identify the causative fungal agents in Covid patients. Methods: A cross-sectional, observational study was conducted at a tertiary care hospital for a period of one and a half years from September 2020 to February 2022. Specimen from 105 clinically suspected cases were collected, processed, and identified by KOH, histopathology, and fungal culture as per standard protocols. Results: Of the total 105 patients, 58 (55.24 %) were diagnosed to have Covid-19 infection. Amongst them, 42 (72.41 %) were confirmed cases of fungal rhinosinusitis. Of the 47 (44.76 %) who did not have Covid-19 infection, 20 (42.55 %) had fungal rhinosinusitis. The significant clinical manifestations observed were nasal obstruction 41 (97.62 %), headache 33 (78.57 %), and nasal discharge 29 (69.05 %). Diabetes mellitus was the major risk factor observed in 36 (85.71 %) of the cases. Maxillary and ethmoid sinuses together were involved in 21 (50 %) cases. Fungi were isolated in 47 of 62 (75.81 %) cases of fungal rhinosinusitis. Aspergillus flavus 13 (22.41 %) was the most common fungi isolated in culture followed by Rhizopus arrhizus 9 (15.52 %). The sensitivity and specificity of KOH were 91.5 % and 74.13 % respectively and that of histopathology were 91.5 % and 94.8 % respectively. Conclusion: In the wake of Covid 19 pandemic, a conjoint collaboration of clinical, radiological, histopathological, and microbiological diagnosis is essential for the proper management of cases.